Pengembangan Media Pembelajaran Comic Book IPA untuk Meningkatkan Keterampilan Berpikir Kritis dan Karakter Peduli Lingkungan - Aniek Kurniawanti Murdianingsih; Sumarno Sumarno; Joko Siswanto (Jurnal Kualita Pendidikan, 2022)
This research is motivated by the low critical thinking skills and environmental care character of students, one of which is the lack of supporting media for interesting learning textbooks with lots of pictures and content that can make it easier for students to understand the material. This study aims to examine and develop a valid, practical and effective science comic book media to improve critical thinking skills and students' environmental care character. This study uses research and development methods, which means that research aims to produce certain products that can be used in the learning process, in the form of science comic book media. The sources of this research are students, teachers, and experts. The data in this study were obtained through data on the needs of students and teachers, which were obtained through a need’s questionnaire; IPA comic book media assessment data, which was obtained through a science comic book media readability questionnaire; and media application data obtained through test instruments, journals, and observation sheets. The data analysis technique used was the research prerequisite test including the normality test, as well as the media effectiveness test including the paired t test and the N-Gain test.The results showed that, (1) the assessment of 1 media expert validator and 2 material expert validators obtained an average percentage score of 95% and 92% with a very valid category; (2) the results of the media practicality test based on the teacher's response obtained an average percentage score of 96% in the very practical category, and based on the student's response the average percentage score was 95% in the very practical category; (3) The results of the T test on the pre-test and post-test of critical thinking skills obtained a Sig score. (2-tailed) of 0.002, while the results of the T-test on the pre-test and post-test of environmental care characters obtained a Sig score. (2-tailed) of 0.000 (4) the results of the N-Gain pre-test and post-test critical thinking skills obtained a score of 0.63 in the "moderate" category, while the environmental care character obtained a score of 0.42 with the category "currently".